The collected visionary teachings of ʼDzi-sgar Mchog-sprul Rdo-rje-drag-po - Rdo-rje-drag-po, ʼDzi-sgar Gter-ston, 1740-1798 (Kargyud Sungrab Nyamso Khang, 1972)
Chiefly comprises ritual texts of an Eastern Tibetan teacher of the Drukpa Kargyudpa tradition of Lamaism.